Stability Evaluation of Micro-Screw Implant in Cases Given a Bone Inducing Substances "An Experimental in Vivo Study - Mustafa M Al-Sultan (University of Mosul, College of Dentistry, 2013)
Aims: The present study aimed to investigate the desirable loading time of micro-screw implant by stability evaluation and detecting the possibility of using alendronate sodium to increase the stability. Materials and methods: Forty eight micro-screw implant, twelve adult rabbits and fourteen alendronate sodium ampoules were used in this study, the rabbits were divided into two main groups, treated and control group, which further subdivided into three subgroups. Eight micro-screw implant instilled in tibiaes of each subgroup just six of them used for test the remaining cancelled, the stability test down using the periotest. These subgroups were nominated according to the loading times which are immediate loading, loading after two weeks and loading after four weeks with stability measured after instillation, before and after loading and two weeks after loading. Results: No significant differences between subgroups before loading and after two weeks of loading but significant after loading. For immediately loaded treated subgroup no significant differences between immediate loading and two weeks after loading. For two and four weeks treated subgroup a significant difference in stability between immediate instillation and after loading. Conclusions: Micro-screw implant even smaller diameter could be used as a fixed anchorage in orthodontics and possibly could be loaded safely from time of immediate instillation, further the use of alendronate sodium add no benefit to increase stability according to the criteria used in this study.